Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | Request PDF - Kulkarni, Atul A.; Vanhamme, Joelle (ResearchGate, 2018)
Request PDF | Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | An experience of surprise is often an outcome of disconfirmation of expectations and can be associated with positive or negative affect depending... | Find, read and cite all the research you need on ResearchGate
Keywords: dept.mrk

Uniting theory and empirical research: market sensing and marketing research - Prince, Melvin; Gabay, G; Priporas, Constantinos; Moskowitz, H (Quantitative research methods in consumer psychology: contemporary and data driven approaches, 2018)
Quantitative consumer research has long been the backbone of consumer psychology producing insights with peerless validity and reliability. This new book addresses a broad range of approaches to consumer psychology research along with developments in quantitative consumer research. Experts in their respective fields offer a perspective into this rapidly changing discipline of quantitative consumer research. The book focuses on new techniques as well as adaptations of traditional approaches and addresses ethics that relate to contemporary research approaches. The text is appropriate for use with university students at all academic levels. Each chapter provides both a theoretical grounding in its topic area and offers applied examples of the use of the approach in consumer settings. Exercises are provided at the end of each chapter to test student learning. Topics covered are quantitative research techniques, measurement theory and psychological scaling, mapping sentences for planning and managing research, using qualitative research to elucidate quantitative research findings, big data and its visualization, extracting insights from online data, modeling the consumer, social media and digital market analysis, connectionist modeling of consumer choice, market sensing and marketing research, preparing data for analysis;, and ethics. The book may be used on its own as a textbook and may also be used as a supplementary text in quantitative research courses.
Keywords: dept.mkt

We beat the cops in GTA: Po(ludic)al activism in the age of video games - Demirbag-Kaplan, Melike; Kaplan-Oz, Begum (Convergence, 2018)
This article explores how individuals reflect on their digital experiences of actualizing fantasies to make sense of their everyday actions, particularly in the context of video gaming. Our study takes a qualitative approach to understanding the context of materializing consumer fantasies, as initially experienced and actualized in video games, and how these fantasies are transformed into material reality, through an investigation of an illustrative case of mass street protests, the 2013 Gezi Protests in Turkey. The findings suggest that digital virtual experiences in video games have obvious manifestations in the material world, as consumers travel on the borders of reality, moving back and forth into the liminoid terrain of the digital virtual, and provide a deeper understanding of how the blurred boundaries between the virtual and material are established in practice.
2 citations (Crossref) [2023-10-31]
Keywords: Digital virtual consumption; Gezi Protests; dept.mkt; liminoid; peer-reviewed; political activism; social movements; video games

How cognitive style influences the mental accounting system: role of analytic versus holistic thinking - Hossain, Mehdi Tanzeeb (Journal of Consumer Research, 2018)
This research examines how people's mental accounting is influenced by their thinking style (analytic vs. holistic). Mental accounting literature shows that people mentally allocate their resources into certain accounts and track expenses against them. The current research, however, finds that while analytic thinkers show such “mental labeling effect,” the holistic thinkers' mental accounting system is flexible. Specifically, analytic thinkers limit their expenses of rebate money to similar category purchases, whereas holistic thinkers show preference for both similar and dissimilar category items (studies 1 and 2). Study 3 shows the mental accounting divergence across analytic- and holistic-thinking groups by examining how they use mental accounting rules in spending gift cards (vs. cash). Study 4 exhibits the underlying psychological process in showing that this effect is attributed to differences in categorization flexibility between the analytic-and holistic-thinking groups. In addition, the above effects are moderated by product type. The divergence in mental accounting between analytic and holistic thinkers is mostly evident in utilitarian (vs. hedonic) consumption instances. Study 5 provides further insights into the moderation effect. The implications of these findings include divergence in cross-category effects of price promotions, and the effect of cross-market discounts between analytic and holistic thinkers.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-545-406-549-464 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.mkt; peer-reviewed

Coffee with co-workers: role of caffeine on evaluations of the self and others in group settings - Unnava, Vasu; Singh, Amit Surendra; Unnava, H Rao (Journal of Psychopharmacology, 2018)
This research explores the effect of consuming a moderate amount of commercially available caffeinated coffee on an individual’s self-evaluated participation in a group activity and subsequent evaluations of the experience. Across two studies, results show that consuming a moderate amount of caffeinated coffee prior to indulging in a group activity enhances an individual’s task-relevant participation in the group activity. In addition, subjective evaluations of the participation of other group members and oneself are also positively influenced. Finally, the positive impact of consuming a moderate amount of caffeinated coffee on the evaluation of participation of other group members and oneself is moderated by a sense of an increased level of alertness.
3 citations (Crossref) [2023-10-31]
Keywords: Caffeine; coffee; dept.mkt; group discussion; peer-reviewed

When nostalgia marketing backfires: Gender differences in the impact of nostalgia on youthfulness for older consumers - Kim, Young Kyu; Yim, Mark Yi-Cheon (Applied Cognitive Psychology, 2018)
Two studies are conducted to test how consumers respond differently in feeling nostalgic depending on age and gender. Study 1 uses narrative writing tasks to empirically test the effect of nostalgic versus nonnostalgic feelings on youthfulness by age and gender. To increase the external validity of our findings in Study 1, Study 2 replicates it using print ads. The results across the two studies consistently reveal a significant effect of nostalgia on feelings of youthfulness that differs by age and gender. Specifically, older women tend to feel less youthful than older men when nostalgic feelings are induced in both studies, whereas younger adults experience no gender difference. Results also show that these differences are explained by self-discontinuity between current and ideal body image. Furthermore, we identify that nostalgic feelings in advertising are effective because they generate positive feelings of youthfulness that in turn result in positive attitudes toward the ad.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000449498200014, lens.org/098-123-730-963-964 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: adult; advertising; age; article; body image; consumer; dept.mkt; female; gender; human; human experiment; male; marketing; nostalgia; peer-reviewed; self-discontinuity; sex difference; youthfulness

Using intuitive awakening for business students to enhance strategic thinking skills - Prince, Melvin; Priporas, Constantinos (Australasian Marketing Journal (AMJ), 2018)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-466-664-601-02X, pop00274, princeUsingIntuitiveAwakening2018a tex.type: [object Object]
Keywords: dept.mkt; peer-reviewed

Relational communication and illusionary loyalty: Moderating role of self-construal - Hossain, Mehdi T; Chonko, Lawrence B (Industrial Marketing Management, 2018)
In this research we demonstrate how various facets of communication influence customer loyalty in a B2B selling environment. Palmatier, Scheer, and Steenkamp (2007) show that salesperson owned loyalty (customers' loyalty specific to the salesperson) can be differentiated from customers' overall loyalty to the firm. We demonstrate how various facets of communication differentially influence salesperson owned loyalty and loyalty to the firm. We find that greater bidirectional flow of communication enhances both salesperson owned loyalty and customers' loyalty to firm. However, greater frequency of communication enhances only salesperson owned loyalty. Formality in communication negatively influences salesperson owned loyalty and positively influence customers' loyalty to firm. In addition, we find an interesting moderation effect of these relationships by customers' self-construal. Theoretical and practical implications of our findings are discussed.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-861-182-258-749 tex.type: [object Object]
Keywords: Communication facets; Loyalty to firm; Relationship marketing; Salesperson owned loyalty; Self construal; dept.mkt; peer-reviewed

Brand archetypes in resource-constrained MBA programmes: A powerful strategic brand management tool - Forbus, Robert; Page, Robert (Journal of Education Advancement & Marketing, 2018)
Keywords: dept.mkt; peer-reviewed; ⛔ No DOI found